Economic Implications of a Protein Transition: Evidence From Walloon Beef and Dairy Farms - Duluins, Océane; Riera, Anton; Schuster, Monica; Baret, Philippe V.; Van den Broeck, Goedele (Frontiers in Sustainable Food Systems, 2022)
In Europe, cattle production is confronted with major challenges across all dimensions of sustainability, urging the need to promote environmentally friendly but also economically viable livestock systems. In addition, animal protein consumption greatly exceeds the dietary guidelines in most European countries. The protein transition, defined as the rebalancing between animal and alternative proteins in diets, is presented as a solution to mitigate the harmful effects of cattle production on the environment, but also as an opportunity to induce healthier diets. Yet, the implications of such a transition on current livestock farmers are still unclear. In this article, we investigate different factors associated with a protein transition (e.g., reduction of herd size, increased concentrate autonomy and increased share of pastures) and assess their implications for the economic performance of dairy and beef farmers in Wallonia, Belgium. In the dairy sector, we find that a reduction in herd size, a higher share of pastures and an increased concentrate autonomy are correlated with lower operating costs, resulting in higher margins. Therefore, a switch to more extensive grazing systems that rely on on-farm fodder production can entail economic benefits for farmers. In the beef sector, on the other hand, farm characteristics are uncorrelated with most economic indicators, but highly associated with subsidies. This suggests that changes in this sector will rather be induced by policy choices than by economic parameters.